2015
DOI: 10.1016/j.cgh.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Varices and Variceal Hemorrhage in Cirrhosis: A New View of an Old Problem

Abstract: The management of portal hypertension in cirrhosis has evolved over time leading to improvements in the care and survival of patients with varices and variceal hemorrhage, particularly in those who achieve a significant reduction in portal pressure. In addition to better treatment strategies and improved therapeutic options, the issue of risk stratification has become essential to identify different patient subpopulations that require a different treatment. We now recognize that the management of varices and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 55 publications
5
59
0
3
Order By: Relevance
“…Decompensated cirrhosis attributed to VB constitutes a high‐risk setting with greater mortality than while in the compensated stage . Mortality is even greater when, in addition to bleeding, patients develop further decompensation of cirrhosis . In keeping with previous uncontrolled studies, our results suggest that HVPG‐guided therapy may improve risk of developing further decompensation, thus contributing to improve survival.…”
Section: Discussionsupporting
confidence: 86%
“…Decompensated cirrhosis attributed to VB constitutes a high‐risk setting with greater mortality than while in the compensated stage . Mortality is even greater when, in addition to bleeding, patients develop further decompensation of cirrhosis . In keeping with previous uncontrolled studies, our results suggest that HVPG‐guided therapy may improve risk of developing further decompensation, thus contributing to improve survival.…”
Section: Discussionsupporting
confidence: 86%
“…As those are frequently associated with ACLF, a higher prevalence of the syndrome could be expected in our cohort (3). In the same way, gastrointestinal hemorrhage was also more common in our ward but there was a trend for bleeding patients to develop ACLF less frequently, probably because they promptly seek medical care and there were major improvements in the management of this condition in recent years (15). The higher prevalence of identified precipitating factors may be related to different diagnostic procedures between the two studies, namely due to the collection of cultures, to the higher prevalence of SBP due to lower compliance to SBP prophylaxis (the most frequent infection) and to a less perfect guideline approach to variceal bleeding outside a randomized controlled trial.…”
Section: Discussionmentioning
confidence: 76%
“…Bacterial infections occur more frequently in cirrhotic patients admitted with gastrointestinal bleeding than for other causes [4,5]. During acute variceal hemorrhage, prophylactic antibiotics are mainstay of treatment [6]. That statement has been approved by our study, since we found significant reduction in T helper and NK cells during the episode of bleeding.…”
Section: Discussionmentioning
confidence: 68%